AKTIVITAS ANTIBAKTERI EKSTRAK DAUN SYZYGIUM POLYANTHUM TERHADAP PSEUDOMONAS AERUGINOSA - Odor Debora Pita Uli Sinaga; Greace Enita Purba; Shela Estica Saragi; Tania Valentina Pasribu; Endang Sulistyarini Gultom (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Bay leaf (Syzygium polyanthum) is a tropical plant from the Myrtaceae family widely used in Indonesian traditional medicine. This study aimed to identify secondary metabolite compounds in bay leaf extract through phytochemical screening and evaluate its antibacterial activity against Pseudomonas aeruginosa. Bay leaf extract was prepared using the maceration method with 96% ethanol. Phytochemical screening was conducted to detect alkaloids, phenolics, flavonoids, terpenoids, tannins, and saponins using standard reagents. Antibacterial activity was tested using the agar well diffusion method at concentrations of 20%, 30%, 40%, and 50%, with chloramphenicol (25 mg) as positive control and 96% ethanol as negative control. Results showed that bay leaf extract contained all tested secondary metabolites. The antibacterial activity test demonstrated inhibition zones of 3.25 mm (20%), 4.05 mm (30%), 6.01 mm (40%), and 6.56 mm (50%), indicating weak to moderate activity. Statistical analysis using one-way ANOVA showed significant differences between concentrations (p < 0.05), with higher concentrations producing larger inhibition zones. The positive control showed strong activity (22.31 mm), while the negative control showed no inhibition. This study confirms that bay leaf extract possesses antibacterial potential against Pseudomonas aeruginosa, with activity increasing proportionally to extract concentration, attributed to synergistic effects of multiple bioactive compounds including flavonoids, tannins, terpenoids, and alkaloids.